Developing an Integrated Diversity Management Navigation System - Munira, Abdul Razak; Najmuddin, Mohd Ramli; Kang, Wei Xian; Wan Suraya, Wan Nik; Zuraina, Ali (Science Publishing Corporation, 2018)
The initiatives of constructive alignment to overcome the TRIPLE CHALLENGES; to embed, engage and entice the technical and engi-neering students in University Malaysia Pahang (UMP) to learn the university core courses of Ethnic Relations have brought both tech-nical and operational challenges. The innovative solution is applying i-E.R.A.T as a 3-in-1 diversity management approach. Despite en-ticing students’ learning interest through the adaptation of Edmodo as one of the e-learning tools, it also supports the university’s educa-tional outcomes on team working, leadership and problem solving; which reflect the National Education Policy on social cohesion. The methodology used to measure the effectiveness of i-E.R.A.T is by performing data analysis via mandatory on-line survey questionnaire called E-Pat that required students’ opinion on the criterion that is related to e-learning. The focus group (FG) as respondents were col-lected from the four sections registered in the researcher’s class of UHM 2022 Ethnic Relations course in Semester 1, session 2015/2016 from a population of approximately two thousand (N=2000) students from 30 sections. The results of the studies showed that majority of the students comprise of more than 90% satisfied (is that, strongly agree and agree) with the implementation of i-E.R.A.T in the teaching and learning processes.